2022
DOI: 10.1155/2022/5495374
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Innovation Strategies, considering Government Subsidy and Altruistic Preference

Abstract: To study the impact of government subsidies and altruistic preferences on green supply chain innovation, Stackelberg game theory and numerical simulation are used to analyze and verify the optimal decision-making of enterprises under different decision-making models. The results show that the two methods of government subsidies can improve product greenness, corporate profits, and overall supply chain performance. While only the unilateral altruistic preference of the manufacturer or retailer can improve produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Barman et al built a green dual-channel supply chain model composed of a supplier, a retailer, and a manufacturer [33]. Liu et al propose two ways of government subsidies to improve the green level, supply benefits, and to guide supply chain members' performance [34]. Hu et al conclude that government needs to give green subsidies to both manufacturers and retailers to improve supply chain performance and environmental impact [35].…”
Section: Green and Sustainable Supply Chainmentioning
confidence: 99%
“…Barman et al built a green dual-channel supply chain model composed of a supplier, a retailer, and a manufacturer [33]. Liu et al propose two ways of government subsidies to improve the green level, supply benefits, and to guide supply chain members' performance [34]. Hu et al conclude that government needs to give green subsidies to both manufacturers and retailers to improve supply chain performance and environmental impact [35].…”
Section: Green and Sustainable Supply Chainmentioning
confidence: 99%
“…Rong et al [44] examined a multinational green supply chain with a dynamic tariff and showed that the altruistic preference of the manufacturer improves the green level of the supply chain. Liu et al [45] addressed the innovative strategies for a green supply chain and concluded that both the altruistic preference of the manufacturer and that of the retailer enhance the product greenness and the overall profit of the green supply chain.…”
Section: Altruism In Agricultural Supply Chainmentioning
confidence: 99%
“…For instance, Wei et al [43] showed that the manufacturer's altruism towards the retailer improves the green level of the supply chain. Liu et al [45] verified that a retailer's altruism towards the manufacturer enhances the product's greenness. The above Corollary 1 demonstrated that consumer-oriented altruism also promotes the green level of agricultural products, although consumers change randomly outside the supply chain, whereas upstream and downstream enterprises interact with each other specifically within the supply chain.…”
Section: Propositionmentioning
confidence: 99%
“…Numerous enterprises exhibit altruistic preferences in their supply chain alliances to foster the system coordination [8][9][10][11][12]. For example, Apple adopts a practice of prepaying suppliers to ensure a steady supply of parts and maintain stable production capacity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous enterprises exhibit altruistic preferences in their supply chain alliances to foster the system coordination [8][9][10][11][12]. For example, Apple adopts a practice of prepaying suppliers to ensure a steady supply of parts and maintain stable production capacity [10]. Toyota offers technical and management support to its suppliers to enhance productivity, while General Motors assists suppliers in upgrading their technologies [11].…”
Section: Introductionmentioning
confidence: 99%